(untitled) (Docentes 2.0 Journal, 2024)
The evidence of difficulties related to the training and strengthening of teachers’ research skills is closely related to their need to constantly improve their pedagogical practice, which stems from certain demands determined by Peruvian society itself. In this sense, the purpose of the study was to determine the link between the research competencies of teachers in secondary educational institutions in the department of Ayacucho and their professional development. Furthermore, it was conducted under the positivist paradigm, hypothetical-deductive method, quantitative approach, non-experimental design, correlational, basic and cross-sectional type, being the population made up of 85 teachers, and the sample of census character, also, for data collection, two questionnaires were used, one containing five dimensions, to measure the research skills and the other with three dimensions to measure professional development. Regarding the results, the existence of a positive and significant relationship was confirmed, and of high potentiality, it was also evidenced that it is significant (r = ,888; p < ,01), as for the non-parametric analysis, the findings were not significantly different from each other (rho = ,815; p < ,01), therefore, it was concluded that the development of research skills seeks to make teachers autonomous and oriented towards the regulation of their learning, providing a basis for the development of their teaching professionalism.